EMOTIONAL INTELLIGENCE OF SCHOOL ADMINISTRATORS IN EDUCATIONAL DEVELOPMENT GROUP 8, RATCHABURI PRIMARY EDUCATIONAL SERVICE AREA OFFICE 1 - Klinnoy, Natthamonkan; Kettanom, Thasporn (Journal of MCU Nakhondhat, 2023)
This research aims to study and find ways to develop the emotional intelligence of school administrators, Educational Development Group 8, Ratchaburi Primary Educational Service Area Office 1, It is a descriptive research. The sample group consisted of 152 teachers form Educational Development Group 8. The tools used were a questionnaire, 5 - level evaluation scale, and a structured interview. It has a reliability value of 0.97 Statistics used in data analysis include: frequency value, percentage, mean, standard deviation and content analysis. The research results found that Overall, the emotional intelligence of school administrators in Educational Development Group 8 is at a high level. When considering each aspect, it was found that all aspects were at the high level, ordered from highest to lowest average as follows: Self - awareness, Self - motivation social skills, Self - control, Understanding the feelings of others. As for the guidelines for developing emotional intelligence of school administrators in Educational Development Group 8, there are guidelines for development as follows: 1) Self - awareness executives should have an understanding of their strengths weaknesses and various aspects of one’s nature according to reality. 2) Self - motivation executives should encourage themselves to think and act creatively. 3) Social skills administrators should have good relationships with personnel in educational institutions and personnel outside educational institutions and the community. 4) Self - control executives should have the ability to control their emotions appropriately by knowing their emotional state correctly. 5) Understanding the feelings of others managers should always be aware of and understand the emotions of others.